1991
DOI: 10.1111/j.1471-4159.1991.tb02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Biochemical Properties of the γ‐Aminobutyric Acid–Benzodiazepine Receptor Protein from Codfish Brain

Abstract: The gamma-aminobutyric acidA (GABAA) receptor of codfish brain has been purified to homogeneity and contains a single polypeptide band of 56 kDa molecular mass. Polyacrylamide gel electrophoresis in sodium dodecyl sulfate (SDS-PAGE) of codfish GABA receptor photoaffinity-labeled by both [3H]flunitrazepam ([3H]Flu) and [3H]muscimol showed a single radioactive peak with molecular mass of 56 kDa, in contrast to the multiple subunits found in other vertebrate species. The codfish receptor, purified using benzodiaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
(52 reference statements)
0
6
2
Order By: Relevance
“…At variance with this study is the finding of Deng et al (1987) on the presence in both fish and mammalian brain of a major radioactive band of 53 kD after photoaffinity labeling with [3H]FNT. However, the same authors, by using irradiation inactivation analysis, have also found important variations between fishes and mammals in the molecular weight of GABA and benzodiazepine receptors (Deng et al, 1987). These findings are consistent with the view that relevant functional and biochemical differences in the GABAA receptor complex may exist between fishes and mammals.…”
Section: I026contrasting
confidence: 65%
See 2 more Smart Citations
“…At variance with this study is the finding of Deng et al (1987) on the presence in both fish and mammalian brain of a major radioactive band of 53 kD after photoaffinity labeling with [3H]FNT. However, the same authors, by using irradiation inactivation analysis, have also found important variations between fishes and mammals in the molecular weight of GABA and benzodiazepine receptors (Deng et al, 1987). These findings are consistent with the view that relevant functional and biochemical differences in the GABAA receptor complex may exist between fishes and mammals.…”
Section: I026contrasting
confidence: 65%
“…In fact, photoaffinity labeling of brain membranes with [3H]flunitrazepam ([3H]FNT) followed by sodium dodecyl sulfate-gel electrophoresis and fluorography has shown mainly a single protein band of 55 kilodaltons (kD) in fishes and two major bands in mammals (Hebebrand et al, 1987). At variance with this study is the finding of Deng et al (1987) on the presence in both fish and mammalian brain of a major radioactive band of 53 kD after photoaffinity labeling with [3H]FNT. However, the same authors, by using irradiation inactivation analysis, have also found important variations between fishes and mammals in the molecular weight of GABA and benzodiazepine receptors (Deng et al, 1987).…”
Section: I026contrasting
confidence: 55%
See 1 more Smart Citation
“…1l In cerebellum, the receptor complexes most likely consist of at least one a subunit together with [3 and ~/subunits. 1,17,20,43,47 Notably, it has been shown that a, 13 and ~/subunits are necessary to form GABAA receptors with the classical functional and regulatory properties. 48 However, the exact subunit composition forming functionally pentameric receptor complexes is still a matter of debate.…”
mentioning
confidence: 99%
“…These processes attenuate sensitivity to excitatory or inhibitory signal transfer reactions in insects, affect normal neural activities, and eventually cause paralysis and death (Wang, ). While the effects of AVM on small animals such as mice (Soderlund et al., ; Krflgek and Zemkovfi, ), rats (Abalis et al., ), guinea pigs (Coccini et al., ), finfish (Deng et al., ; Lumaret et al., ), and mammals (Robertson, ) and the distribution of GABA A R in C. gibelio have been studied (Ruan et al., ), the effects of AVM on C. gibelio remain unknown. Therefore, this paper investigated the effects of different medium lethal concentrations of AVM on the protein expression of GABA A R in C. gibelio by Western blot and immunohistochemistry methods.…”
Section: Introductionmentioning
confidence: 99%